Oxide formation mechanism of a corrosion-resistant CZ1 zirconium alloy. (1st June 2023) - Hu, Jing; Lin, Weitong; Lv, Qingyang; Gao, Changyuan; Tan, Jun
Highlights: CZ1 alloy has superior corrosion resistance beyond Zr-4 and improved Zr-4 alloys. Lowering Sn and Nb contents give rise to the less tetragonal ZrO2 phase in oxides. Low-density lateral cracks reduce the diffusion route for oxidating species. Second-phase particles relieve the metal-to-oxide transformation-induced stresses. Tailoring microstructure and microchemistry enables the deceleration of corrosion. Abstract: Tailoring microstructure and microchemistry by altering elemental compositions and thermomechanical treatment parameters enables superior corrosion performance in zirconium alloys for nuclear applications. However, our understanding of the relationship between various defects and the corrosion process remains limited in the newly developed zirconium alloys. Here we report the oxide formation mechanism of a CZ1 zirconium alloy with corrosion resistance surpassing many other zirconium alloy systems, such as Zircaloy-4 and Zr-1Nb-1Sn alloys. Autoclave experiments of CZ1 alloy and Zr-1Nb-1Sn model alloy were performed in 360 °C water for up to 820 d. We quantitively determined oxide phases by transmission Kikuchi diffraction (TKD) and examined lateral cracks, nano-porosity, and second-phase particles in oxide scales by transmission electron microscopy (TEM). Compared to the Zr-1Nb-1Sn model alloy, CZ1 alloy with lower Nb and Sn concentrations has shown smaller and lower-density lateral cracks but slightly larger oxide grains, reducing the diffusion route for oxidating species. Using analytical scanning and transmission electron microscopy, we demonstrate that due to the lower content of Sn (∼0.9 wt.%), there is less tetragonal ZrO2 phase formed in the oxide, and the level of tetragonal to the monoclinic phase transition is reduced. Although the Nb content (0.1 wt.%–0.3 wt.%) is lower than the solid solution limit of Nb in Zr, by introducing minor elements such as Fe, Cr, and Cu, there are still a reasonable number of second-phase particles to relieve the high stress associated with the metal-to-oxide transformation. These mechanisms have substantially changed the density and distribution of lateral cracks in the oxide, thus reducing the corrosion rate of zirconium alloys.